ANALISA KEGIATAN BERHITUNG PADA ANAK DENGAN MEDIA SPINDLE BOX DI TK AISYIYAH 18 ASEMJAJAR - Gusmaniarti Gusmaniarti; Amanatul Lisanika Fatiya Nur Rosyidah; Hikmia Nur Insyia Novalia Pringadi; Rifaul Fajeriyah (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2022)
Early childhood education is useful as a stimulation for children in accordance with the growth characteristics of children at their age. Age 4-5 years is the age when children begin to recognize symbols in the form of numbers from one to ten. Therefore, early childhood education, especially in formal education such as in Aisyiyah 18 Asemjajar Kindergarten, must be able to improve the learning of arithmetic activities. Spindle Box is an educational game tool for children that will be implemented in Aisyiyah 18 Asemjajar Kindergarten to improve counting activities. This research was conducted on 18 children in class A1 (9 boys and 9 girls). Research activities were carried out for three days with predetermined steps. Based on the results of the study, the spindle box succeeded in increasing children's numeracy activities and the children became more enthusiastic so it can be concluded that the APE spindle box has a positive influence on children's numeracy activities in Aisyiyah 18 Kindergarten Asemjajar